1998
DOI: 10.1007/s004170050123
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the sympatho-vagal interaction in central serous chorioretinopathy measured by power spectral analysis of heart rate variability

Abstract: These results support the view that the pathogenesis of CSC is related to an increase in the sympathetic activity of the autonomic nervous system. Furthermore, the LF/HF ratios seem to correlate with the activity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 12 publications
3
36
1
Order By: Relevance
“…24,25 Moreover, a type A personality and sympathetic hyperactivity frequently characterize these patients, easily leading to changes in systemic hemodynamics and OPP. 26,27 New OCT technologies have substantially improved our capability in qualitatively and quantitatively evaluating the choroidal vasculature and perfusion. 28,29 OCT-Angiography (OCT-A), a recent label-free imaging modality that uses the blood cells motion as contrast, is able to provide information on the blood flow in the chorioretinal microvasculature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Moreover, a type A personality and sympathetic hyperactivity frequently characterize these patients, easily leading to changes in systemic hemodynamics and OPP. 26,27 New OCT technologies have substantially improved our capability in qualitatively and quantitatively evaluating the choroidal vasculature and perfusion. 28,29 OCT-Angiography (OCT-A), a recent label-free imaging modality that uses the blood cells motion as contrast, is able to provide information on the blood flow in the chorioretinal microvasculature.…”
Section: Resultsmentioning
confidence: 99%
“…A dysfunction of the autonomic nervous system is widely recognized in people affected by CSCR. 27 Compared to healthy subjects, CSCR patients have a higher sympathetic tone, associated with type A personality, easy emotional stress, and high levels of catecholamines in the blood. 16,26 Psychological stress and increased BP are found strictly linked in people with sympathetic hyperactivity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an association between CSC and increased sympathetic activity [6], higher levels of catecholamine [7] and high blood pressure [6]. Since OSAS causes an increase in sympathetic activity and may increase cortisol levels [9,14], it can be speculated that patients with OSAS are at higher risk of developing CSC than the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors including psychological stress and type-A behaviour [3], corticosteroids [4] and sympathomimetic use [5] have been reported to induce or exacerbate CSC. Patients with CSC demonstrated increased heart-rate variability as a marker of sympathetic activity compared to controls [6]. Additionally, there are several reports of increased corticosteroid and catecholamine levels in these patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…The R-R interval data of 20 consecutive 256-beat intervals were then subjected to power spectral analysis using the autoregressive model (ProBeat, Access pro med, Vaduz, Liechtenstein) [17]. This method was chosen instead of fast Fourier transformation because with autoregressive algorithms, shorter segments can be reliably analysed.…”
Section: Power Spectral Analysismentioning
confidence: 99%